You Make Me Sick: Abuse at Work and Healthcare Utilization. Issue 3 (8th August 2022) - Thompson, Merideth; Carlson, Dawn; Crawford, Wayne; Kacmar, K. Michele; Weaver, Sally
ABSTRACT: Though research on abuse at work is abundant, abusive supervision's effects on healthcare utilization and outcomes remains unknown. We use two working samples ( n 1 = 701; n 2 = 155) to test abusive supervision's effects on subjective health perceptions and objective health and healthcare utilization (i.e., chronic illness and pain medications/diagnoses and number of visits to a medical professional). We argue that work-family balance and burnout serially mediated these effects. Using surveys and electronic health records, we find support tying abusive supervision to both subjective and objective health outcomes. Integrating logic from gender socialization theory, we argue (and find support) for the moderation of these effects by gender, such that the relationships are stronger for men. We conclude with future research directions and organizational implications.